MENINGKATKAN CITRA KABUPATEN GARUT MELALUI PLACE BRANDING SERTA DAMPAKNYA TERHADAP KEPUTUSAN MENGUNJUNGI DESTINASI PARIWISATA - Utrasih, Henny; Lestari, Fitri (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
The purposes of the research are: (1) to know the idea of place branding, (2) to know the idea of the decision to visit a tourism attraction, (3) to know the influence of place branding upon the decision to visit a tourism attraction. The object of the research is the domestic tourists who visit one of twenty nine tourism attractions in Garut. The method used in this research is verified descriptive. The data source used in this research is primary and secondary. From the total population of 2.442.147 people, the researcher takes the sample of a hundred people. The probability sampling, especially cluster sampling, is a sampling technique that the researcher chooses. The data collection technique is held through interview, observation, questionnaire, and literature study. To scale how much the influence of place branding upon the decision to visit a tourism attraction, the researcher uses the data analysis technique of path by using software SPSS 18. keyword: place branding, Garut, destination